PEMAHAMAN DAN PENGHAYATAN SPIRITUALITAS SANTA ANGELA MERICI DALAM KOMUNITAS SUSTER URSULIN DI KOTA MADIUN - Ladesti, Jessica Dwi; Ardijanto, Don Bosco Karnan (Bahasa Indonesia, 2025)
This research is motivated by the interest of the researcher to recognize how far the Ursuline Sisters deepen and internalize the spirituality of Saint Angela Marici as a founder of the Congregation of Santa Ursula. This research aims to describe and explain the understanding and internalization of the spirituality of Santa Angela Marici in the community life of Ursuline Sisters in Madiun City.To answer the objectives of this research, the researcher interviewed 6 informants Ursuline Sisters who are members of the Ursuline Sisters Community in Madiun City. Those informants are chosen using a Purposive Sampling Technique. This research took place from March 1-31, and it was done using Quantitative Research Methodology. The results of the research conclude that all the Ursuline Sisters understand and internalize the spirituality of Saint Angela Marici in living their Holy Vocation. The sisters are living out this spirituality through double love: love for God and love for neighbors. The internalization of love for the neighbors shown among those is through the accompaniment rendered to all the students of Santa Ursula’s Girls” Dormitory. The kinds of accompaniment are expressed through the openness to the presence of all the students at the dormitory, teaching a life of appreciating others and food, accompanying studying activity, teaching a simple lifestyle, involving in decision-making, positioning themselves as responsible mother for daily life of all the students at the dormitory, getting to know each student’s personality at the dormitory, acting decisively, positioning themselves as a friend, and becoming living example to all the students at the dormitory.